Improved salivary cortisol rhythm with dual-release hydrocortisone - Ceccato, Filippo (Endocr Connect, 2018)
INTRODUCTION AND AIM: The purpose of replacement therapy in adrenal insufficiency (AI) is mimicking endogenous cortisol levels as closely as possible: dual release hydrocortisone (DR-HC) has been introduced to replicate the circadian cortisol rhythm. Multiple daily saliva collections could be used to assess the cortisol rhythm during real life: our aim was to study the salivary cortisol profile in AI. MATERIALS AND METHODS: We prospectively evaluated, in an observational study, 18 adult outpatients with AI (11 primary and 7 secondary AI), switched from conventional treatment (conv-HC, 25 mg/day) to the same dose of DR-HC. We collected six samples of saliva in a day, measuring cortisol (F) and cortisone (E) with LC-MS/MS. Forty-three matched healthy subjects served as controls. RESULTS: F levels were similar in the morning (and higher than controls) in patients treated with conv-HC or DR-HC; otherwise F levels and exposure were lower in the afternoon and evening in patients with DR-HC, achieving a cortisol profile closer to healthy controls. Daily cortisol exposure, measured with area under the curve, was lower with DR-HC. Morning F and E presented sensitivity and specificity >90% to diagnose AI (respectively threshold of 3 and 9.45 nmol/L). Total cholesterol and HbA1c levels reduced with DR-HC. CONCLUSIONS: Salivary cortisol daily curve could be used as a new tool to assess the cortisol profiles in patients treated with conv-HC and DR-HC. A lower daily cortisol exposure was achieved with DR-HC (despite the same HC dose), especially in the afternoon-evening.